Game efficiency of elite male sitting volleyball players with regard to athletes` physical impairment - Marszalek, J.; Molik, B.; Gomez, M.-A. (International Journal of Sports Science & Coaching, 2018)
The aim of this study was to illustrate differences in game efficiency in sitting volleyball of male and female elite athletes in terms of players` impairment. Game analysis was conducted during World Championships in Sitting Volleyball in 2014. Modified Game Performance Sheet for Sitting Volleyball was used to assess players` actions: attack, serve, block, block of serve, defense, and ball receiving. Coleman`s formulas were counted to obtain game efficiency of athletes. In statistics, Kruskal-Wallis test and Bonferroni correction were used (p value was set equal .005 and .003, respectively, in male and female group). 128 male and 91 female sitting volleyball athletes were included into this study. They were divided into groups in terms of impairment. There were no statistically significant differences in anthropometric parameters in male and female groups of players. Also, there were not statistically significant differences in game efficiency between players with different impairments in male as well as in female groups. This study did not confirm the current classification system in sitting volleyball (division into minimal disabled and disabled athletes). There is a need to continue research and find more evidences to substantiate or to change the current classification procedures in classification system in sitting volleyball.